Obstetric Patients in Intensive Care Unit - Keleş, Gönül Tezcan; Topçu, İsmet; Kefi, Arzu; Ekici, Zeynep; Sakarya, Melek (Fırat University, 2006)
Objectives: We analyzed retrospectively all obstetric admission to determine the causes and outcomes of intensive care unit. Materials and Methods: In this study; 18 obstetric patient referred to ICU from 1999 to 2005 in pregnancy and/or postpartum period, were evaluated by observing demographic data, admittance reasons, interventions in ICU and clinical outcomes. Results: Incidence of obstetric cases in ICU was obtained as 2.7%. 13 cases (72.2%) were delivered from other hospitals. ICU requirement rate is 1 per 421 deliveries. Mean age of 18 patients is 27.4±5.4 years. ICU stay is 4.6 days and median APACHE II score is 7. There were differences APACHE II score between survivors and non-survivors (p

Amaç: Bu çalışmanın amacı Yoğun bakım ünitesine (YBÜ)'ne alınan obstetrik olguları retrospektif olarak değerlendirmek, YBÜ'ne kabul sıklığını, nedenlerini ve klinik sonuçlarını araştırmaktır. Gereç ve Yöntem: Yoğun bakım ünitesine (YBÜ) 1999-2005 yılları arasında gebe ve/veya postpartum dönemde yatırılan 18 obstetrik olgunun retrospektif demografik verileri, kabul nedenleri, yoğun bakımda yapılan girişimleri ve klinik sonuçları incelenerek değerlendirilmeye alındı. Bulgular: Obstetrik olguların YBÜ'ndeki sıklığı %2.7 olarak bulundu. 13 olgu (%72.2) diğer hastanelerden sevk edilmiştir. Yoğun bakım kullanma oranımız 421 doğumda 1'dir. 18 olgunun ortalama yaşı 27.4±5.4'tür. Yatış süreleri 4.6 gün ve APACHE II skoru orta değeri 7'dir. Yaşayan ile yaşamayan olgular arasında APACHE II skorları farklı bulundu (p
Yoğun Bakım Ünitesinde Obstetrik Olgular